Simulation Study on the 3D Layout and Optimization Method of Metro Station Entrances/Exits Considering Rainfall Factors - LUO Lan; CHEN Jinjie; LYU Xikui (Chengshi guidao jiaotong yanjiu)
［Objective］ The rational layout of metro station entrances and exits plays a crucial role in enhancing the efficiency of urban rail transit systems. To address the limitations of conventional 2D evaluation methods, due to the lack of intuitiveness and authenticity in assessments, a 3D metro station entrance model is integrated with a city′s 3D environment to simulate rainfall scenarios. ［Method］ By combining BIM (building information modeling) technology with the UC win/Road 3D software, urban 3D scenes are rapidly constructed. On the foundation of urban 3D scene construction and rainfall simulation, BIM API secondary development technology is utilized to explore 3D visualization methods for simulating and optimizing metro station entrance/exit layouts. This approach achieves seamless integration of metro station BIM models with urban 3D environments. The reasonableness of entrance positions, elevations, and other parameters is evaluated from a 3D visual perspective, addressing the shortcomings of current 2D evaluation and simulation methods for metro station entrance exit layouts. ［Result & Conclusion］ Simulation results show that this method effectively showcases the alignment between urban rail transit and city planning, as well as the elevation configurations of metro stations. By incorporating regional meteorological data and differentiated rainwater drainage network data of the planned area, the study provides a novel approach for the rational planning and layout of metro station entrances and exits is provided, offering valuable reference insights for practical applications.